Objective Evaluation of Obstacle Perception Using Spontaneous Body Movements of Blind People Evoked by Movements of Acoustic Virtual Wall - Yoshikazu Seki; Kiyohide Ito (Human Behavior and Emerging Technologies)
Obstacle perception using sound is the ability to detect silent objects, such as walls and poles. It is very important for blind people to recognize their environment using acoustic information through their auditory sense when walking or conducting various daily activities. In this paper, to develop an objective method for evaluating the degree of obstacle perception acquisition in the education and rehabilitation of the blind, the authors measured the spontaneous body movements evoked by the approach of an acoustic virtual wall. Ten blind persons who have experienced obstacle perception in their daily life, and seven sighted persons with no such experience participated in the experiment. The reciprocal (approach and receding) movements of the virtual wall were presented using simulated reflected sound, and the spontaneous body movements of the subjects were measured. As the results indicate, eight of the ten blind participants showed large maximum values for the correlation function between the wall and their body movements, whereas six of the seven sighted participants showed small maximum values. These results indicate that body movements can be used for an objective evaluation of obstacle perception. In particular, it was determined that the maximum value of the correlation function is the most appropriate for such an evaluation, because it does not depend on the subject’s physique.